Impact of airflow limitation in chronic heart failure - Bektas, S. (Neth Heart J, 2017)
BACKGROUND: Comorbidities are common in chronic heart failure (HF) patients, but diagnoses are often not based on objective testing. Chronic obstructive pulmonary disease (COPD) is an important comorbidity and often neglected because of shared symptoms and risk factors. Precise prevalence and consequences are not well known. Therefore, we investigated prevalence, pulmonary treatment, symptoms and quality of life (QOL) of COPD in patients with chronic HF. METHODS: 205 patients with stable HF for at least 1 month, aged above 50 years, were included from our outpatient cardiology clinic, irrespective of left ventricular ejection fraction. Patients performed post-bronchodilator spirometry, a six-minute walk test (6-MWT) and completed the Kansas City Cardiomyopathy Questionnaire (KCCQ). COPD was diagnosed according to GOLD criteria. Restrictive lung function was defined as FEV(1)/FVC ≥0.70 and FVC <80% of predicted value. The BODE and ADO index, risk scores in COPD patients, were calculated. RESULTS: Almost 40% fulfilled the criteria of COPD and 7% had restrictive lung disease, the latter being excluded from further analysis. Noteworthy, 63% of the COPD patients were undiagnosed and 8% of those without COPD used inhalation therapy. Patients with COPD had more shortness of breath despite little difference in HF severity and similar other comorbidities. KCCQ was significantly worse in COPD patients. The ADO and BODE indices were significantly different. CONCLUSION: COPD is very common in unselected HF patients. It was often not diagnosed and many patients received treatment without being diagnosed with COPD. Presence of COPD worsens symptoms and negatively effects cardiac specific QOL.